Cancer risk in Japanese Crohn's disease patients: Investigation of the standardized incidence ratio. Issue 8 (22nd July 2013) - Yano, Yutaka; Matsui, Toshiyuki; Hirai, Fumihito; Okado, Yuki; Sato, Yuho; Tsurumi, Kozue; Ishikawa, Satoshi; Beppu, Tsuyoshi; Koga, Akihiro; Yoshizawa, Naoyuki; Higashi, Daijiro; Futami, Kitaro
Abstract Background and Aim There have been very few reported investigations on the standardized incidence ratio (SIR) of intestinal cancer and all cancers other than intestinal cancer with Crohn's disease (CD) by organ in Japan. This study examined the risk of developing cancer (i.e. SIR) that occurs in association with CD. Methods The subjects were 770 CD patients managed at our hospital department, which specializes in inflammatory bowel disease, during the approximately 25 years from July 1985 to August 2010. The number of expected cancer patients in a healthy population matched for sex and age with the CD patients in our hospital was then calculated. The relative risk, or SIR, was also calculated. Results The total observation period was 10 552 person‐years, during which 19 cases (2.5%) of cancer were discovered in 770 subjects. The cancer cases included nine cases of colorectal cancer (CRC), one case of small bowel cancer, one case of stomach cancer, three cases of acute myeloid leukemia, two cases of endometrial cancer, one case of lung cancer, one case of skin cancer, and one case of thyroid cancer. The SIR for cancers in Japan in 2003 was 0.87 (95% confidence interval [CI] 0.52–1.35) for all cancers, 2.79 (95% CI 1.28–5.29) for CRC, and 6.94 (95% CI 1.43–20.3) for leukemia. Conclusions Among the cancers in CD patients in our hospital, no significant difference was seen in the risk for all cancers in comparison with the standard population. However, the risks for CRC and leukemia were significantly higher than in the standard population.